Assessment of ecotoxicological hazard and risk of groundwater contamination with different groups of pesticides - Stavnichenko P.V.; Novohatska L.O.; Antonenko A.M.; Vavrinevych O.P. (Medičnì Perspektivi)
The aim of our work was to determine ecotoxicological risk of herbicides, insecticides, fungicides of different chemical classes with different mechanisms of action by the method of Melnikov M.M. and leaching potential index by the method of Sergeev S.G. and co-workers. It was established that in soil and climatic conditions of Ukraine ecotoxicological hazard of studied herbicides by (1-6) orders of magnitude, fungicides – by (3-5) orders, insecticides – by (2-3) orders lower than DDT. The least ecotoxic are herbicides of the last generations, then fungicides and the most ecotoxic are insecticides and herbicides of the old first generations. It was proved the high danger of groundwater contamination with studied herbicides, insecticides and fungicides, except for mesotrione, the application of which has moderate danger in the soil and climatic conditions of Ukraine. It was shown that in soil and climatic conditions of Ukraine, ability of migration from the soil into groundwater of metribuzin, thiamethoxam, paclobutrazole is high, topramezone and mesotrione – moderate, for other substances – low; in terms of hygienic standards in the ground itallows to avoid them getting into the soil flow and minimize the danger of groundwater contamination to public health.